Identification of Amphibian Species in the Durin Serugun Village Forest, Sibolangit, North Sumatra - Tambunan, Muhammad Iqbal H.; Haq, Muhammad Daffa; Muammar, Muammar; Hardiansyah, Dadang; Ritonga, Yusran Efendi (Fakultas Kehutanan Universitas Mulawarman, 2025)
Durin Serugun Village Forest, Sibolangit District, North Sumatra is a customary and conservation forest. Located in Deli Serdang Regency and is the headwaters of important rivers in Medan. This area contains a wealth of flora and fauna diversity such as amphibians that have never been published. A study was conducted in April 2025 with a Visual Counter Survey (VES) combined with exploration to obtain data on amphibian species in two habitats; terrestrial (including arboreal and fossorial) and aquatic. The results of the study obtained 15 species of amphibians from 5 families; Bufonidae (4 species), Megophrydae (1 species), Ranidae (4 species), Digroclossidae (5 species), Rhacophoridae (1 species). Three of them are endemic to Sumatra; Chalcorana parvaccola, Sumatrana crassiovis and Rhacophorus catamitus. The report on amphibians in this location is expected to be an important reason for all related parties to take firm and serious steps in protecting and preserving the area and in more in-depth exploration the area has the potential to reveal the existence of amphibian species due to the lack of data in this potential location.